Etruscan Gold Appliances: Origins and Functions as Indicated by an Example from Orvieto, Italy, in the Danish National Museum - Marshall Joseph Becker (Dental Anthropology Association, 1994)
The ancient Etruscans invented the dental bridge over 2,500 years ago. The earliest known example, made from pure gold, was excavated from the ancient site of Satricum in central Italy. it has been dated to ca. 630 BC. At that time this village was within the Etruscan realm. All of the earliest examples of these dental prostheses derive from Etruscan contexts. Study of all of the known dental appliances from this part of the ancient world suggests that their use faded as central Italy came under Roman influence. Among the 19 known prostheses from Etruscan archaeological contexts (Becker, nda) is an outstanding example, believed to be from Orvieto, now in the Danish National Museum in Copenhagen (Figs. 1, 2) (Becker, 1992). A detailed description of the Copenhagen example allows it to be compared with other known pieces. We now have a clear understanding of the various ways in which prostheses were made and used. A significant discovery is that these Etruscan bridges were worn only by females, suggesting that cosmetics and vanity were important dental concerns. The unusual construction technique of the Copenhagen piece and its place within the typology of examples reflects the evolution of this technology over more than 400 years.